إزالة النفط من سطح المياه باستخدام الطحالب البحرية (Latakia University Journal -Basic Sciences Series, 2014)
تهدف هذه الدراسة إلى إلقاء الضوء على استخدام الطحالب البحرية ورقائق البولي بروبلين لإزالة النفط الخام من مياه البحر السطحية. حدد زمن الامتصاص الأمثل و السعة الامتصاصية لهذه المواد في حمام نفط/ماء ونفط فقط بدون ماء لثلاثة أنواع من النفط ذات لزوجة مختلفة. ارتبطت القدرة على إزالة النفط من سطح مياه البحر ببنية المادة الماصة وخواص سطحها إضافة إلى كمية وخواص النفط وبشكل خاص لزوجته. بينت الدراسة أن زيادة زمن الامتصاص لا يؤثر على السعة الامتصاصية للمواد المدروسة بوجود نوعي النفط ذي اللزوجة المنخفضة والمتوسطة (LV و MV)، بينما ازدادت السعة الامتصاصية لهذه المواد عند زيادة زمن الامتصاص إلى 30 دقيقة بوجود الفيول HV. تجاوزت القدرة الامتصاصية للطحلب Enteromorpha القدرة الامتصاصية للطحالب البحرية الأخرى، بينما سجلت رقائق البولي بروبلين أعلى سعة امتصاصية. ازدادت السعة الامتصاصية للمواد المدروسة بشكل عام مع ازدياد لزوجة النفط. تشابهت السعات الامتصاصية للمواد المدروسة بوجود النفط فقط مع السعات الامتصاصية لهذه المواد بوجود النفط والماء. تبين هذه النتائج إمكانية استبدال المواد المصنعة المستخدمة لإزالة النفط من الأوساط البحرية باستخدام الطحالب البحرية كونها ذات سعة امتصاصية عالية نسبياً.The aim of this study is to highlight the potential use of marine algae as well as polypropylene for the removal of crude oil from surface seawater. The determination of optimal sorption time and sorption capacity of the materials in oil/water bath and oil bath without water in presence of three oils of different viscosity were investigated. The capacity of oil removal from seawater was related to structure and surface properties as well as oil amount and oil properties especially, its viscosity. The results revealed that the extension of absorption time does not influence absorption capacity of the examined sorbents in presence of both oils of low and middle viscosity (LV and MV). Nevertheless, the sorption capacity was increased by extending the absorption time to 30 min. For high viscose oil (HV). The sorption capabilities of Enteromorpha exceeded those observed for all of the other algae, while polypropylene fiber showed the highest capacity. Overall, the sorption capacity of the studied sorbents increased with increasing oil viscosity. The absorption capacities of studied materials in the oil bath and oil/water bath were comparable. The results suggested that substitution of synthetic oil sorbents used in Syria by marine algae is possible in oil removal, which have relatively high sorption capacity.